South-South student migration: Socially integrating students from Portuguese-speaking Africa at UNILAB, Brazil - Cairns, D.; França, T. (Globalisation, Societies and Education, 2020)
The Brazilian University for International Integration of the Afro-Brazilian Lusophony (UNILAB) was created to host students from Portuguese-speaking Africa and Brazil. In this article, we look at the aims and objectives of UNILAB, which include the social integration of these students at the university. We present results from interviews conducted at UNILAB in 2018 with 63 international and domestic students. Analysis of this material shows that despite acknowledgement of the value of internationalization at UNILAB, the social integration level of Portuguese-speaking students from outside Brazil at the university is characteristically weak among the interviewees, a situation they attribute to a lack of suitable preparation for staff at the host institution and prejudice towards African students in the local community. We consider what these findings mean for the future of UNILAB and the development of Global South-South student migration.